The Effect of the Schwarz Rearrangement on the Periodic Principal Eigenvalue of a Nonsymmetric Operator - Nadin, Grégoire (SIAM journal on mathematical analysis, 2010)
This paper is concerned with the periodic principal eigenvalue $k_λ(μ)$ associated with the operator $-\frac{d^2}{dx^2}-2λ\frac{d}{dx}-μ(x)-λ^2$, where $λ\in\mathbb{R}$ and $μ$ is continuous and periodic in $x\in\mathbb{R}$. Our main result is that $k_λ(μ^*)≤ k_λ(μ)$, where $μ^*$ is the Schwarz rearrangement of the function $μ$. From a population dynamics point of view, using reaction-diffusion modeling, this result means that the fragmentation of the habitat of an invading population slows down the invasion. We prove that this property does not hold in higher dimension if $μ^*$ is the Steiner symmetrization of $μ$. For heterogeneous diffusion and advection, we prove that increasing the period of the coefficients decreases $k_λ$, and we compute the limit of $k_λ$ when the period of the coefficients goes to 0. Last, we prove that in dimension 1, rearranging the diffusion term decreases $k_λ$. These results rely on some new formula for the periodic principal eigenvalue of a nonsymmetric operator.